2018
DOI: 10.5588/ijtld.17.0498
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome with a short multidrug-resistant tuberculosis regimen in nine African countries

Abstract: The study results support the use of the short regimen recently recommended by the World Health Organization. Its high level of success even among HIV-positive patients promises substantial improvements in TB control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
129
7
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 13 publications
20
129
7
4
Order By: Relevance
“…This points to advanced HIV disease as a driver of higher risk of death in HIV-MDR-TB coinfected patients. This finding highlights the importance of providing timely HIV comprehensive care and treatment to HIV-MDRTB coinfected patients, and corroborates findings of a recent systematic review and meta-analysis [21] and other studies [22,30,31] that reported a high mortality rate in this patient population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This points to advanced HIV disease as a driver of higher risk of death in HIV-MDR-TB coinfected patients. This finding highlights the importance of providing timely HIV comprehensive care and treatment to HIV-MDRTB coinfected patients, and corroborates findings of a recent systematic review and meta-analysis [21] and other studies [22,30,31] that reported a high mortality rate in this patient population.…”
Section: Discussionsupporting
confidence: 90%
“…The treatment success rate in our study was also significantly better than the results of a previous meta‐analysis reporting treatment success rates in the range of 62–63.48% . The treatment success rate of 90.5% in the group of patients treated with shorter MDR‐TB regimen is also greater than the 82% reported in a study evaluating the treatment outcome with the same regimen in nine African countries . The high treatment success rate observed in this study could be the result of the improvements recently made by the programme in a number of interventions whose individual relative contribution could not be determined with our findings.…”
Section: Discussioncontrasting
confidence: 80%
“…This MDR-TB cohort was treated with a shorter course regimen similar to that recommended by the WHO; those with pyrazinamide resistance had a nonstatistically significant trend toward higher failure. 27 According to a meta-analysis examining pyrazinamide resistance from MDR-TB cohorts across eight WHO regions, pooled prevalence ranged from 49% (Western Pacific) to 80% (Eastern Mediterranean), and 53% in the Americas. 28 Among RR TB culture isolates from 12 sub-Saharan African countries, the prevalence of pyrazinamide resistance was 52% overall, ranging from 21% in Togo to 80% in Burkina Faso.…”
Section: Discussionmentioning
confidence: 99%
“…Gatifloxacin has been withdrawn from the market owing to reports of associated dysglycaemia. A prospective observational study of a modified Bangladesh regimen comprising standard‐dose (400 mg once daily) moxifloxacin instead of high‐dose gatifloxacin has demonstrated high treatment success rates among second‐line treatment‐naïve MDR‐TB patients . STREAM Stage 1, a randomized controlled trial, has evaluated a modified Bangladesh regimen that contains high‐dose (maximum 800 mg once daily) moxifloxacin instead of high‐dose gatifloxacin in comparison with the longer 20‐month fluoroquinolone‐based MDR‐TB treatment regimen recommended by the World Health Organization.…”
Section: Adverse Reactions To Moxifloxacinmentioning
confidence: 99%